ADOPTION LEVEL OF IMPROVED DAIRY HUSBANDRY PRACTICES AND CONSTRAINTS IN RURAL AREAS OF SURAT DISTRICT - A. B. Fulsoundar, G. P. Sabapara (Indian Journal of Animal Production and Management, 2017)
The present study was conducted in the Surat district of Gujarat. Total 300respondents were interviewed for the questionnaire prepared about improved dairyhusbandry practices adopted by them and constraints in adoption of those practices. Thefindings indicated that majority of dairy farmers had medium adoption level on differentcomponent of improved dairy husbandry practices viz. 62.33% for housing, 65.33% forfeeding, 57% for breeding, 62.34% for healthcare, 68.33% for milking management and 70%for calf rearing. The overall adoption levels of the respondents in improved dairy husbandrypractices fall under low, medium and high categories are 9.33%, 75.34% and 15.33%,respectively. The adoption index of different aspect of improved dairy husbandry practices ofhousing, feeding, breeding, health care, milking and calf rearing were 44.97, 40.90, 64.98,51.55, 50.60 and 50.85%, respectively and overall adoption index of improved dairyhusbandry practices was 50.64% which indicated medium adoption level of dairy farmers inthe study area. The majority of dairy farmers had high construction cost (94%), lack of owncapital (64%), high cost of feed (97.33%), non-availability of green fodder round the year(85.33%), lack of awareness about treatment of poor quality straw to improve its nutritivevalue (68.67%), repeat breeding problems in dairy animals (88.67 %), non-remunerativeprice for milk (93.67%), lack of knowledge in clean milk production (71.33%), high cost ofveterinary medicine (78.67%), problem of mastitis in dairy animals (71.33%) and inadequateknowledge of diseases and their control (67.33%) were major constraints in adoption ofimproved dairy husbandry practices.Keywords: Adoption, Constraint, Dairy Husbandry, Practices, Surat district.